Antimicrobial Activity of Ethanol Extract of Pinang Seed (Areca catechu L.) Against the Growth of Candida albicans and Malassezia furfur Fungi Using the Agar Diffusion Method - Naid, Tadjuddin; Saputri, Febrianti Ayu; Nuryanti, Siska (Journal Microbiology Science, 2025)
Pinang seeds (Areca catechu L.) are known for their various benefits, including antimicrobial properties. This study aims to evaluate the antimicrobial activity of ethanol extract from pinang seed against the growth of Candida albicans and Malassezia furfur fungi using the agar diffusion method. The research involved extracting the pinang seed using maceration with 96% ethanol, followed by evaporation using a rotary vacuum evaporator to obtain a concentrated extract. Antimicrobial activity was tested across concentrations of 32%, 16%, 8%, 4%, 2%, 1%, 0.5%, and 0.1%. The results showed that at a concentration of 32%, the ethanol extract produced the largest inhibition zones: 27.78 mm against Candida albicans and 15.51 mm against Malassezia furfur, both categorized as very strong activity. These findings suggest that ethanol extract of pinang seed has significant potential as an antimicrobial agent, particularly against fungal pathogens.